Minimum dietary diversity and associated factors among children aged 6-23 months in Addis Ababa, Ethiopia - Dagmawit Solomon; Zewdie Aderaw; Teketo Kassaw Tegegne (BMC, 2017)
Abstract Background Dietary diversity has long been recognized as a key element of high quality diets. Minimum Dietary Diversity (MDD) is the consumption of four or more food groups from the seven food groups. Globally, only few children are receiving nutritionally adequate and diversified foods. More than two-thirds of malnutrition related child deaths are associated with inappropriate feeding practice during the first two years of life. In Ethiopia, only 7 % of children age 6-23 months had received the minimum acceptable diet. Therefore, the main aim of this study was to determine the level of minimum dietary diversity practice and identify the associated factors among children aged 6-23 months in Addis Ababa, Ethiopia. Methods A health facility based cross sectional study was undertaken in the three sub-cities of Addis Ababa from 26th February to 28th April, 2016. A multi-stage sampling technique was used to sample the 352 study participants or mothers who had children aged 6-23 months. Data were collected by using a structured and pretested questionnaire, cleaned and entered into Epi info 7 and analyzed using SPSS 24 software. Logistic regression was fitted and odds ratio with 95% confidence interval (CI) with p-value less than 0.05 was used to identify factors associated with minimum dietary diversity. Result In this study, the overall children with minimum dietary diversity score were found to be 59.9%. Mother's educational attainment and a higher household monthly income were positively associated with the minimum dietary diversity practice. Similarly, mothers' knowledge on dietary diversity and child feeding was positively associated with minimum dietary diversity child feeding practice, with an adjusted odds ratio of 1.98 (95% CI: 1.11-3.53). Conclusion In this study, the consumption of minimum dietary diversity was found to be high. In spite of this, more efforts need to be done to achieve the recommended minimum dietary diversity intake for all children aged between 6 and 23 months.